2010
DOI: 10.1103/physreva.81.052120
|View full text |Cite
|
Sign up to set email alerts
|

Classical correlation and quantum discord sharing of Dirac fields in noninertial frames

Abstract: The classical and quantum correlations sharing between modes of the Dirac fields in the noninertial frame are investigated. It is shown that: (i) The classical correlation for the Dirac fields decreases as the acceleration increases, which is different from the result of the scalar field that the classical correlation is independent of the acceleration; (ii) There is no simple dominating relation between the quantum correlation and entanglement for the Dirac fields, which is unlike the scalar case where the qu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
96
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 107 publications
(102 citation statements)
references
References 47 publications
5
96
1
Order By: Relevance
“…So far, most of the works have only considered spinless fields, either bosonic or fermionic [5][6][7][8][9][10][11][12][13][14][15][16][17][18]22]. Only a few works have considered fields of non-zero spin in this context, only in very specific cases (spin 1/2) [14,26,27], and always assuming the single mode approximation.…”
Section: Introductionmentioning
confidence: 99%
“…So far, most of the works have only considered spinless fields, either bosonic or fermionic [5][6][7][8][9][10][11][12][13][14][15][16][17][18]22]. Only a few works have considered fields of non-zero spin in this context, only in very specific cases (spin 1/2) [14,26,27], and always assuming the single mode approximation.…”
Section: Introductionmentioning
confidence: 99%
“…Some inchoate ideas about this topic were presented in quantum optics [6]. On the other hand, with the rise of relativistic quantum information, much attention has been concentrated on the behavior of quantum correlations in a relativistic setting [7][8][9][10][11][12]. These works provide us some new way in understanding the quantum theory.…”
Section: Introductionmentioning
confidence: 99%
“…Sibasish Ghosh showed that it is not possible to discriminate between any three Bell states if only a single copy is provided and if only local operations and classical communication are allowed [14]. At present most of the studies consider only one of the Bell states but ignore the other three [9][10][11][12][13]15,16] because different Bell states will give the same result without considering environment. On the other hand, Philip Walther and Anton Zeilinger realized a probabilistic for Bell state analyzer for two photonic quantum bits by use of a non-destructive controlled-NOT gate based on entirely linear optical elements [17].…”
Section: Introductionmentioning
confidence: 99%
“…In order to do that, we will define a quantum discord for fermionic particles. Previous studies of quantum discord in systems of indistinguishable particles, like in [20], employ the notion of correlation of modes [6], which are distinguishable. This paper is organized as follows.…”
Section: Introductionmentioning
confidence: 99%